Development of Learning Activity Management for Creative Writing Using Concept Map, Thai Language Learning Substance in 6th Graders - Thipyotha, Phinyapass (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were: 1. to develop the learning activity for Grade 6 Students’ on creative writing using concept map approach with the efficiency of 80/80, 2. to find the effectiveness index of learning activity, 3. to compare the students’ creative writing between before and after learning based on concept map approach, and 4. to study Grade 6 students’ satisfaction on this learning. The target group was 24 students in grade 6 from Bannongseaw School by cluster sampling technique. The research instruments were 1) the lesson plans, 2) the learning achievement test, and 3) the satisfaction questionnaire. The research revealed that: 1) The efficiency of learning activity was 85.04/82.08 as the specified criterion 80/80, 2) The effectiveness index the learning activity was 0.7500, 3) The comparative findings of the students’ posttest scores were significantly higher than the pretest scores at .05 level, and 4) students’ satisfaction in learning for creative writing by using the concept map at the highest level.